2020
DOI: 10.1161/circulationaha.119.044359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Canagliflozin on Cardiovascular and Renal Events in Patients With Type 2 Diabetes Mellitus and Chronic Kidney Disease According to Baseline HbA1c, Including Those With HbA1c <7%

Abstract: We thank all participants, investigators, and trial teams for their participation in the trial. The CREDENCE study was sponsored by Janssen Research & Development, LLC, and was conducted collaboratively by the sponsor, an academic-led Steering Committee, and an Academic Research Organization, George Clinical. Analyses were performed by George Clinical and independently confirmed by the sponsor. Technical editorial assistance was provided by Kimberly Dittmar, PhD, of MedErgy, and was funded by Janssen Global Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 6 publications
3
63
0
1
Order By: Relevance
“…Nevertheless, kidney protection is consistent and substantial in this population (14). SGLT2 inhibitors also have kidney benefits in people with well-controlled glycemia (HbA 1c ,7%) in whom further glucose lowering was minimal (15). In the DAPA-HF trial, which included people with or without diabetes, the effects on HF and kidney disease end points were consistent regardless of diabetes status (16).…”
Section: Mechanisms Of Kidney Protection By Sglt2 Inhibitorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, kidney protection is consistent and substantial in this population (14). SGLT2 inhibitors also have kidney benefits in people with well-controlled glycemia (HbA 1c ,7%) in whom further glucose lowering was minimal (15). In the DAPA-HF trial, which included people with or without diabetes, the effects on HF and kidney disease end points were consistent regardless of diabetes status (16).…”
Section: Mechanisms Of Kidney Protection By Sglt2 Inhibitorsmentioning
confidence: 97%
“…SGLT2 inhibitors promote diuresis due to glucosuria and natriuresis (34). Diuresis is an important mechanism for reducing blood pressure and risk for HF events (11)(12)(13)(14)(15)(16)35). Lack of a compensatory increase in heart rate suggests commensurate blunting of sympathetic nervous system activity, which may also contribute to salutary effects of SGLT2 inhibitors compared with other diuretics (36,37).…”
Section: Diuresis and Natriuresismentioning
confidence: 99%
See 1 more Smart Citation
“…However, for patients attaining glycemic targets with metformin alone, addition of an SGLT2i (particularly, if both agents are used in low doses) is not likely to cause hypoglycemia and may still provide kidney and cardiovascular benefits. Kidney and cardiovascular benefits are not proven in this specific population but are supported by the observations that SGLT2i reduce kidney and cardiovascular events similarly across the full range of studied HbA1c levels ($6.5%) [239][240][241][242][243][244] and that beneficial effects of dapagliflozin and empagliflozin on heart failure (among patients with heart failure with reduced ejection fraction [HFrEF]) did not require presence of diabetes. 240,244a More data are needed to confirm or correct use of this approach in CKD.…”
Section: Research Recommendationsmentioning
confidence: 98%
“…Authors found a 30% reduction in the primary composite outcome (end-stage kidney disease, doubling of serum creatinine, or death from renal or CV causes) [54]. Additionally, similar results were found in patients with more advanced renal impairment (eGFR 30e45 ml/min/1.73 m 2 ) at baseline and across all levels of baseline HbA1c, including 650 patients with HbA1c levels below 7% [55]. The results translate into a number-neededto-treat (NNT) of 19, which is lower than that reported in previous studies with ARB alone [56].…”
Section: On Renal Functionmentioning
confidence: 68%